PERKEMBANGAN ARSITEKTUR VERNAKULAR ATONI; KASUS STUDI: KAWASAN ISTANA KERAJAAN AMARASI DI TEUNBAUN, KABUPATEN KUPANG - El Boru, Jeky (Universitas Atma Jaya Yogyakarta, 2013)
Abstract: This research concerns about the development of vernacular Atonian architecture in an architecture and urban context. The samples were taken from some villages that are still applying Atonian architecture and still have been changed until now. The method used in data collecting are observation, interview, and from the literature sources. The analytical method used is qualitative description which is concern about any sources of research in vernacular Atonian culture. It is compared to the current condition of Atonian culture by using the categorization of cultural forms which were mentioned by Koentjaraningrat. This research aims is to find out the changes of architecture and urban context in the development of vernacular Atonian architecture, The result of this research is the changes on cultural forms which can be seen in three manifestation, that are the changes in idea (cultural system), activities, and artifacts as physical things in building and urban planning context.Keywords: development, architecture and urban, vernacular Atonian architectureAbstrak: Tulisan ini membahas mengenai perkembangan arsitektur vernakular Atoni dilihat dari sisi arsitektur dan kawasan. Kasus studi penelitian ini menekankan pada kawasan kampung yang masih mengunakan arsitektur Atoni dan juga yang telah mengalami perubahan. Metode pengumpulan data dilakukan melalui observasi, wawancara, dan melihat berbagai sumber pustaka, sedangkan metode analisis yang diterapkan, yakni deskripsi kualitatif dengan melihat berbagai sumber penelitian kebudayaan vernakular Atoni yang kemudian dibandingkan dengan perubahan yang terjadi pada kebudayaan Atoni saat ini dengan mengacu pada kategorisasi wujud kebudayaan yang diungkapkan oleh Koentjaraningrat. Tujuan penelitian ini adalah mengetahui perubahan arsitektur dan kawasan dalam perkembangan arsitektur vernakular Atoni, dan hasil dari penelitian ini adalah perubahan kebudayaan dilihat dari tiga wujud yakni perubahan Â pada tata cara, aktivitas, dan benda-benda berupa bangunan dan tata kawasan.Kata kunci: perkembangan, arsitektur dan kawasan, arsitektur vernakular Atoni